2018
DOI: 10.1371/journal.pone.0200319
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of circulating RSV strains among subjects in the OUTSMART-RSV surveillance program during the 2016-17 winter viral season in the United States

Abstract: BackgroundRespiratory syncytial virus (RSV) is an established cause of serious lower respiratory disease in infants, elderly and high-risk populations. The OUTSMART surveillance program aims to characterize patient populations and currently circulating RSV strains, and monitor temporal and geographic evolution of RSV F and G proteins in the U.S.MethodsThe OUTSMART 2016–17 study collected RSV-positive samples from 25 RSVAlert® laboratories from 4 U.S. regions and Puerto Rico during November 2016 through March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Unlike the seasonal circulation of RSV that is generally observed in temperate 1618 and tropical climates 1921 , RSV-A circulated almost throughout the year, similar to observations made in Senegal in 2012 and 2013 but not 2014 22 . PIVs, and IVs in particular, circulated for shorter periods of time.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Unlike the seasonal circulation of RSV that is generally observed in temperate 1618 and tropical climates 1921 , RSV-A circulated almost throughout the year, similar to observations made in Senegal in 2012 and 2013 but not 2014 22 . PIVs, and IVs in particular, circulated for shorter periods of time.…”
Section: Discussionsupporting
confidence: 80%
“…PIVs, and IVs in particular, circulated for shorter periods of time. The predominance of one particular RSV type in one season, namely RSV-A in 2015, was similar to that observed in Mali (RSV-B in 2013) 23 , Senegal (RSV-B in 2012, RSV-A in 2013, RSV-B in 2014) 22 , Ghana (RSV-B in 2006 and 2013, RSV-A in 2014) 21 , and the United States (RSV- in 2015) 16 .…”
Section: Discussionsupporting
confidence: 69%
“…Studies on RSV subtypes from around the world have consistently found the RSV-A subtype to be more common; additionally, RSV-A is thought to have higher transmissibility than RSV-B [21–23]. While previous studies have found much variability in subgroups, and others have described a predominance of RSV-B during outbreaks [24], this is the first burden of disease study finding RSV-B as the dominant subtype, suggesting that RSV subtype selection may vary more between populations than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…The RSV genome encodes 11 proteins, two of which, surface proteins F and G, are the major targets of neutralizing and non-neutralizing antibodies. RSV can be further divided into subtypes A and B which co-circulate at approximately the same rate [ 12 ]. Subtype differences are based on antigenic and genetic variability of the G protein, whereas F maintains greater than 90% sequence identity between groups [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%